Implementation of Augmented Reality Booklet Based on Problem Based Learning on Earth and Solar System to Increase Students' Scientific Literacy Skills: Penelitian - Masudatut Toyyibah; Agung Mulyo Setiawan; Firda Awalia Putri; Safwatun Nida (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to improve students' scientific literacy on Earth and Solar System material through the use of Augmented Reality (AR)-based booklets integrated with the Problem-Based Learning (PBL) model. Scientific literacy is an important ability in science education, especially to understand abstract concepts and natural phenomena scientifically. The method used in this research is pre-experimental design with one-group pretest-posttest, involving 32 seventh grade students in one of the public junior high schools in Malang City. The instrument used was a scientific literacy description question based on the 2025 PISA framework, which has been validated by experts and field tested. The results showed a significant increase in the average score of students' scientific literacy after treatment, from the "sufficient" category at the pretest to "moderate" at the posttest. This shows that the integration of AR technology and PBL approach in booklet media can improve students' scientific understanding, critical thinking skills, and interest in learning about Earth and Solar System material.